2021
DOI: 10.21203/rs.3.rs-555480/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quercetin Synergistically Potentiates the Anti-Angiogenic Effect of 5- Fluorouracil on HUVEC Cell Line

Abstract: background: Since tumors need oxygen and nutrients to grow and spread, angiogenesis has an essential role in cancer growth and metastasis. So, inhibition of angiogenesis at the initial stage of cancer is a critical strategy in metastasis inhibition. 5-Fluorouracil (5-FU) is a chemotherapy drug that has also been shown to have anti-angiogenic effects. Quercetin, a natural polyphenolic compound, has anti-angiogenic effects. The present study was conducted to investigate the enhancement of the anti-angiogenic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Paeonol and its metabolites had anti-inflammatory and antioxidant effects by blocking the MAPK/ERK/p38 signaling pathway [ 66 ]. Quercetin inhibited TNF-α induced MAPK pathway activation, also had anti-angiogenic effects, which inhibited expression of proinflammatory factors and endothelin1 [ 67 69 ]. These datas suggested that paeonol, quercetin, paeoniflorin and oxypaeoniflorin may be the active components of RMC for cooling and promoting blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Paeonol and its metabolites had anti-inflammatory and antioxidant effects by blocking the MAPK/ERK/p38 signaling pathway [ 66 ]. Quercetin inhibited TNF-α induced MAPK pathway activation, also had anti-angiogenic effects, which inhibited expression of proinflammatory factors and endothelin1 [ 67 69 ]. These datas suggested that paeonol, quercetin, paeoniflorin and oxypaeoniflorin may be the active components of RMC for cooling and promoting blood circulation.…”
Section: Discussionmentioning
confidence: 99%